Policy Responses to Low Fertility in Serbia. The Case of the Municipality of Bela Palanka - Jelena ŽIVKOVIĆ; Tamara LUKIĆ; Anđelija IVKOV-DZIGURSKI; Tatjana DJEKIĆ (Transylvanian Review of Administrative Sciences, 2017)
This article deals with the issue of low fertilityin Serbia. In the case of the municipality of BelaPalanka, the authors made an attempt to establishthe actual causes of this phenomenon andto examine the attitudes of the female populationconsidering their decision against parturition,i.e. giving birth to more children. Based on theresearch results, some measures of populationpolicy are proposed which can be implementedat the local level. The same measures can beapplied in the case of any other municipality inSerbia with a similar demographic situation.